ANALISIS PERBEDAAN KINERJA KEUANGAN RUMAH SAKIT SWASTA NON RUJUKAN COVID SEBELUM DAN SELAMA PANDEMI COVID-19 (STUDI KASUS DI RUMAH SAKIT XY BANGIL) - Umi Setyorini (Institut Teknologi dan Bisnis Yadika, 2021)
Performance measurement is one of the most important factors for a company. These measurements are used to assess the success of the company and as a basis for preparing rewards or incentives within So far, performance measurement has been carried out traditionally and only focuses on the financial side and the number of patients decreases and of course affects the financial performance of XY Hospital. Cost Recovery Rate is one of the financial performance indicators used by XY Hospital to measure financial performance. CRR is the percentage comparison between the total income compared to the total production costs incurred by the hospital. The population of this study is all the number of patients before the covid-19 pandemic and during the covid-19 pandemic in 2019 and 2020, all the number of human resources before the covid-19 pandemic and during the covid-19 pandemic in 2019 and 2020, all the amount of income before the covid pandemic -19 and during the 2019 and 2020 covid- 19 pandemic. Inpatient services, namely obstetrics & gynecology treatment rooms, child care rooms, baby rooms, general care rooms have decreased from 2019 to 2020. Inpatient services, namely obstetric & gynecological treatment rooms, child care rooms, baby rooms, general care rooms have decreased from 2019 to 2020. Outpatient services for general poly, emergency care installations, obstetrics & obstetrics specialist poly, children, internal medicine, general surgery, eye, THT, lung, nerve, surgery, skin & genital, heart, maternal & child health/ family planning have decreased from 2019 to 2020. Medical Support Services in the laboratory have increased from 2019 to 2020 because every Patients who come to the IGD must have a rapid test. For radiology services, pharmacy experienced a decrease in the number of patients from 2019 to 2020. In 2020 it decreased to diploma (D3) by 5.4%, while the S1 level was 9.1% and the S2 level was 1.9%. Cost Recovery Rate (CRR) or the company's ability to finance the operations of XY Hospital In 2020 it decreased by 13.71% from 2019, still below the target (CRR = 100%) this indicates that XY Hospital in 2020 suffered a loss this is due to The number of patients decreased due to the pandemic.